Climatic factors as determinants of international migration - Michel Beine; Christopher Parsons (Center for Economic Studies and ifo Institute (CESifo), 2012)
We examine environmental factors as potential determinants of international migration. We distinguish between unexpected short-run factors, captured by natural disasters, as well as long-run climate change and climate variability. Building on a simple neo-classical model we use a panel dataset of bilateral migration flows for the period 1960-2000, the time and dyadic dimensions of which additionally allow us to control for numerous time-varying and time invariant factors. As a whole, we find little direct impact of climatic change on international migration in the medium to long run across our entire sample. Using the rate of urbanization as a proxy for internal migration we find strong evidence that natural disasters beget greater flows of migrants to urban environs.
Keywords: F22; O15; 330; international migration; climate change; natural disasters; income maximization; Klimaveränderung; Naturkatastrophe; Internationale Wanderung; Binnenwanderung; Landflucht; Einkommen; Migrationstheorie; Schätzung; Welt